1997
DOI: 10.1128/mcb.17.11.6609
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and functional collaboration of p300 and C/EBPβ

Abstract: Transcriptional coactivators such as p300 and CREB-binding protein (CBP) function as important elements in the transcription factor network, linking individual transactivators via protein-protein interactions to the basal transcriptional machinery. We have investigated whether p300 plays a role in transactivation mediated by C/EBP␤, a conserved member of the C/EBP family. We show that C/EBP␤-dependent transactivation is strongly inhibited by adenovirus E1A but not by E1A mutants defective in p300 binding. Ecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
294
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(314 citation statements)
references
References 51 publications
18
294
2
Order By: Relevance
“…We next wanted to investigate why histone acetylation levels were low in PU.1 Ϫ/Ϫ cells and in PUER cells at early time points of OHT induction. This was not due to the absence of nucleosomes, as shown by a ChIP (23,37), and work from our lab demonstrated that active c-fms regulatory elements recruit CBP (9). It has been shown previously that the activity of CBP can be regulated as well (35); it was therefore possible that CBP was recruited but was inactive.…”
Section: Resultsmentioning
confidence: 81%
“…We next wanted to investigate why histone acetylation levels were low in PU.1 Ϫ/Ϫ cells and in PUER cells at early time points of OHT induction. This was not due to the absence of nucleosomes, as shown by a ChIP (23,37), and work from our lab demonstrated that active c-fms regulatory elements recruit CBP (9). It has been shown previously that the activity of CBP can be regulated as well (35); it was therefore possible that CBP was recruited but was inactive.…”
Section: Resultsmentioning
confidence: 81%
“…Although Myb and CREB bind the same domain of CBP (Dai et al, 1996;Kiewitz and Wolfes, 1997;OelgeschlaÈ ger et al, 1996), the interaction with Myb proteins is constitutive rather than phosphorylation-dependent (Dai et al, 1996;OelgeschlaÈ ger et al, 1996). Interestingly, CBP and p300 can also interact with and stimulate the activity of C/EBPb (Mink et al, 1997;OelgeschlaÈ ger et al, 1996), suggesting that the coactivators may act as a bridge between Myb and C/EBPb (Figure 1). This type of bridging activity could explain the ability of Myb proteins to cooperate with C/EBPb and a wide variety of other transcription factors, in the context of di erent promoters.…”
Section: Cbp and P300mentioning
confidence: 99%
“…This type of bridging activity could explain the ability of Myb proteins to cooperate with C/EBPb and a wide variety of other transcription factors, in the context of di erent promoters. CBP and p300 bind the transactivation domains of c-Myb and C/EBPb, located in their central and N-terminal domains, respectively (Dai et al, 1996;Kietwitz and Wolfes, 1997;Mink et al, 1997;OelgeschlaÈ ger et al, 1996). This suggests that the coactivators are involved in mediating the transactivation activity of Myb and C/EBPb.…”
Section: Cbp and P300mentioning
confidence: 99%
“…They have a recognized function as transcriptional coactivators for diverse families of transcription factors, including the nuclear steroid receptors (Chakravarti et al, 1996;Hanstein et al, 1996;Kamei et al, 1996;Yao et al, 1996), and bHLH Mutoh et al, 1998;Qiu et al, 1998;Sartorelli et al, 1997;Yuan et al, 1996), leucine zipper (Bannister and Kouzarides, 1995;Bannister et al, 1995;Chrivia et al, 1993;Mink et al, 1997), and zinc ®nger (Blobel et al, 1998;Lee et al, 1995) proteins. Acting as transcriptional adaptors, they link sequence-speci®c DNA-binding proteins to components of the basal transcriptional machinery (Abraham et al, 1993;Kee et al, 1996;Nakajima et al, 1997) and to proteins with histone acetyltransferase activity (Yang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%